Build iOS Database Apps with Swift and SQLite - Languedoc, Kevin (Apress : Imprint: Apress, 2016)
This book leads you through the essential concepts and new iOS 10 SDK and Swift 3 programming language APIs to build iPhone and iPad database driven applications using the defacto standard for data storage for mobile apps, SQLite. Readers will learn about SQL operations like selecting, inserting, updating and deleting data using various data types like text, numerical types, images and even audio/video data. After working through this book, you will gain an expert view of developing iOS apps using SQlite as a data storage using Objective-C and Swift. With Build iOS Database Apps with Swift and SQLite you will also gain expert knowledge on how to create databases at runtime, including creating or modifying indexes, triggers, tables, columns, and views. The examples use time-tested code from working applications.